Behavioral Biases and Investment Decision: A Systematic Literature Review - Amgain, Pushpa Nidhi (Kanya Journal, 2024)
This study aims to provide comprehensive overview of traditional finance theories, introducing and emphasizing the significance of behavioral finance, examining the behavioral biases and how they contribute to the risk-averse and risk-seeking attitudes and proposing a future research direction through the construction of a taxonomy model of investor’s psychology in the form of a causal framework that impact on investment decision. The study employed a systematic literature review approach and includes 23 research articles from Google scholar database in the fields of behavioral finance and investment decision. The time frame from 2008 to 2023 and the choice of 2008 as the base period is justified by the global financial crisis. The findings suggest that a comprehensive overview of the literature on behavioral finance and investors psychology behavioral biases impact on investment decision and theoretical developments. The taxonomy model contributes to understanding the complex interplay of behavioral biases influencing investment decision. A proposed a taxonomy model, categorizing various biases as independent variables including emotional, cognitive, and financial biases. The findings revealed irrational behavior in stock markets, influenced by factors like fear-based sentiments and artificial intelligence. The research emphasized the significance of moderating variable as financial literacy and risk perceptions as mediating variable and research implication for investors, portfolio managers, and policymakers. Future studies can explore behavioral biases in different investor groups and examine regional variations in developing and developed countries.